TELECOMMUNICATIONS ENGINEERING STUDENTS' LEARNING STYLES USING WHATSAPP MEDIA DURING THE COVID-19 SCHOOL YEAR 2020-2021 - Umniyatul Azizah; Ahmad Akhyar Ariz; Rizki Firdaus (IAIN Padangsidimpuan, 2023)
Coronavirus appeared in early March 2020 in Indonesia. For this reason, learning uses WhatsApp media at Telkom University. How is the relationship between learning styles adjusted during the covid 19 period and the use of WhatsApp? This research uses a quantitative approach with a population of 110 people and 10% is taken as a sample so that the sample is 11 people. There is a significant relationship between learning styles and the use of WhatsApp media. This is evidenced in the SPSS results using the Kolmogorov-Smirnov test, the results of normal data and a relationship of 0.08 means this is greater than 0.05 and it proves that there is a relationship between learning styles and learning to use WhatsApp media during the covid 19 periods.